Circadian rhythm of glucose uptake in cultures of skeletal muscle cells and adipocytes in Wistar-Kyoto, Wistar, Goto-Kakizaki, and spontaneously hypertensive rats - Feneberg, Reinhard; Lemmer, Björn (Chronobiology international, 2004)
Hypertension and noninsulin-dependent diabetes mellitus are usually associated with marked glucose intolerance. Hypertensive and even nonhypertensive diabetic individuals display disturbances of the normal circadian blood pressure rhythm. However, little is known about circadian changes of the glucose uptake in muscle and fat cells, the major glucose utilizing tissues. Therefore, we investigated circadian rhythms of glucose uptake in primary muscle and fat cell cultures of hypertensive and type II diabetic rats and their respective control strains. 2-Deoxy-d-(1-3H)glucose uptake was measured over 48 h after synchronization of cells by means of medium change with and without addition of insulin, phloretine, and/or staurosporine. The circadian changes of glucose uptake were assessed by fitting cosine curves to the uptake values. Insulin stimulation of deoxyglucose uptake was only present in control animals, not in hypertensive and diabetic rats. Deoxyglucose uptake displayed a circadian rhythm in control animals, and was markedly disturbed in hypertensive and diabetic animals. Blocking of glucose transporters by phloretine abolished the circadian pattern of deoxyglucose uptake indicating a role of glucose transporters in its generation. Inhibition of kinases by staurosporine inhibited the insulin-stimulated deoxyglucose uptake, but did not dampen the circadian rhythmicity of basal deoxyglucose uptake. The generation of the circadian rhythm of glucose uptake in muscle and fat cell cultures is therefore probably insulin independent and independent of protein kinases. In summary, our results show for the first time: (a) a circadian rhythm of deoxyglucose uptake in glucose utilizing muscle and fat cells in vitro, (b) a disruption of this rhythm in cells of hypertensive and diabetic rats.